Effects of perivitelline fluid obtained from horseshoe crab on the proliferation and genotoxicity of dental pulp stem cells - Musa, Marahaini; Mohd Ali, Khadijah; Thirumulu Ponnuraj, Kannan; Ahmad, Azlina; Omar, Nor Shamsuria; Chatterji, Anil; Mokhtar@Makhtar, Khairani Idah (Royan Institute, 2015)
Objective: Perivitelline fluid (PVF) of the horseshoe crab embryo has been reported to possess an important role during embryogenesis by promoting cell proliferation. This study aims to evaluate the effect of PVF on the proliferation, chromosome aberration (CA) and mutagenicity of the dental pulp stem cells (DPSCs). Materials and Methods: This is an in vitro experimental study. PVF samples were collected from horseshoe crabs from beaches in Malaysia and the crude extract was prepared. DPSCs were treated with different concentrations of PVF crude extract in an 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay (cytotoxicity test). We choose two inhibitory concentrations (IC50 and IC25) and two PVF concentrations which produced higher cell viability compared to a negative control (100%) for further tests. Quantitative analysis of the proliferation activity of PVF was studied using the AlamarBlue® assay for 10 days. Population doubling times (PDTs) of the treatment groups were calculated from this assay. Genotoxicity was evaluated based on the CA and Ames tests. Statistical analysis was carried out using independent t test to calculate significant differences in the PDT and mitotic indices in the CA test between the treatment and negative control groups. Significant differences in the data were P<0.05. Results: A total of four PVF concentrations retrieved from the MTT assay were 26.887 mg/ml (IC50), 14.093 mg/ml (IC25), 0.278 mg/ml (102% cell viability) and 0.019 mg/ml (102.5% cell viability). According to the AlamarBlue® assay, these PVF groups produced comparable proliferation activities compared to the negative (untreated) control. PDTs between PVF groups and the negative control were insignificantly different (P>0.05). No significant aberrations in chromosomes were observed in the PVF groups and the Ames test on the PVF showed the absence of significant positive results. Conclusion: PVF from horseshoe crabs produced insignificant proliferative activity on treated DPSCs. The PVF was non-genotoxic based on the CA and Ames tests.